BENTUK DAN FUNGSI ENDE MANDIDENG PADA MASYARAKAT DESA KAMPUNG BARU KABUPATEN MANDAILING NATAL SUMATERA UTARA - Mangunsong, Melani Eklesia; Manggala, Bondan Aji (Institut Seni Indonesia Surakarta, 2023)
The article “The Form and Function of Ende Mandideng in the Community of Kampung Baru Village,Mandailing Natal Regency, North Sumatra”, is a presentation of a study to answer two problems, (1) what is the form of Mandideng singing in the community of Kampung Baru Village, North Panyabungan District, Mandailing Natal Regency, Province North Sumatra, and (2) how the Mandideng song functions in the culture of the people of Kampung Baru Village. The research in this article applies qualitative research methods using field research methods under the umbrella of Budilinggono and Alan’s theory. P. Merriam about the form of serving as well as function and uses. According to Budilinggono, the presentation form analyzes melodic phrases in songs and song structures related to rhythmic, melodic and time signature motifs. According to Merriam, an analysis of use and function includes a discussion of how music is used in human activities and the reasons why music is used. The results of the research in this article state that Ende Mandideng, in content analysis, reveals the concept of moral instillation in children. In terms of its function, Ende Mandideng has five functions, namely: (1) emotional expression function, functioned to express the parents’ love for their children when putting the child to sleep, (2) entertainment function, functioned as a reliever of parents’ boredom from their daily activities, ( 3) communication function, functions as a means of conveying messages through songs sung by parents to their children, (4) function of strengthening adjustment to social norms, this function can explain that Mandideng songs have the power to instill the child’s mindset. children from childhood in accordance with applicable social norms, especially regarding social norms related to the relationship between children and parents, (5) the function of preserving and stabilizing culture, functioning as the preservation of folk songs which are currently almost being displaced by developments over time.